Factors affecting the Staff Turnover and its Impact on Quality Care in Tertiary Care Hospital - Farzana Mehboob Ali, Atiyyah Adeel, Wasif Masood, Sofia Noreen, Danish Ahmed, Danish Ali Siddiqui (Pakistan Journal of Medical & Health Sciences, 2023)
Background: When hospital staff leave their positions, it may be difficult to satisfy patients’ demands and maintain a good standard of care, which in turn can put more pressure on the remaining staff. The outcome may be a dramatic shift in how nurses conduct in their employment, with repercussions including decreased job satisfaction, decreased productivity, and even employee turnover. Objective: The goal of this research was to identify the causes of staff turnover in tertiary care hospitals. Methods: shaheed mohtarma benazir Bhutto institute of trauma a tertiary care hospitals in karachi,participants were included in a cross-sectional study, from 01/05/2022 to 31/10/2022. Participants had to be registered staff with at least a year of experience working in a clinical environment at either hospital. Quota sampling was used to pick staff from hospitals, stratified by shift, with signed informed permission from each participant. Information was gathered by a self-administered questionnaire with four parts (Brooks’ assessment of QNWL, Anticipated Turnover Scale (ATS), free-form questions, and demographic details). Results: A total 80 participants were recruited to carry out the present study. According to the cutoff for willingness to depart as determined by the ATS (> 3.5), 61% of people are interested in finding another employment. Hospital employees were more likely to be dissatisfied with their quality of life on the job if the QNWL cutoff satisfaction level (≤4.2) was lower. There was an equal gap in discontentment between men and women on the quality of their work lives. There is a considerable increase in work dissatisfaction among participants between the ages of 31-40 (19%) (P0.000). Nonetheless, those between the ages of 41- 50 accounted for the largest percentage of respondents (21%) who were interested in leaving their current place of employment. Conclusion: Because of the implications and effects on patient care, the QNWL and nurse turnover pose serious difficulties for healthcare organizations. Keywords: staff turnover, survey-base, quality of life, Tertiary hospital